Analisa Maksimum Produksi dalam Pemenuhan Kebutuhan Konsumen Serta Perhitungan Laba Usaha Pada Industri Batu Bata Usaha Baru Desa Sungai Buluh Kecamatan Muara Bulian - Ratumas Hartha Delima; Nadiatul Khoiroh (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2020)
The title of this research is the Analysis of Maximum Production in Meeting the Needs of Consumers as well as the Calculation of Business Profits in the New Business Brick Industry Sungai Buluh Village, Muara Bulian District. The purpose of this study was to determine the analysis of production development, sales volume, and operating profit in the new brick industry of Sungai Buluh Village. Data analysis method is using quantitative descriptive approach. Intended for the problem by describing the data obtained through observation, interviews in the literature in accordance with the problems studied. Data obtained directly from employees and leaders of the New Business Bricks Industry. The results of the study that the authors found in the field are as follow. From the data of the development of new brick business production in Sungai Buluh Village in 2018-2019, the production development experienced an instability every month. The highest increase occurred in November 2018, an increase of 33%. Then the lowest increase occurred in September 2018 5.6% with an average production development of 0.005%. And If seen from the data development of potential business demand for new brick businesses in Sungai Buluh Village in 2018-2019, the development of potential demand on a monthly basis is experiencing instability. The highest increase occurred in November 2018, an increase of 5,0%. And then the lowest increase was only 5,6% due to the decline in purchasing power of new business products in Sungai Buluh Village with an average potential growth of 2,4%. When viewed from the sales volume data at the New Business Bricks Company is unstable or up and down. The highest increase of 11,4% was due to many factors, one of which was the increase in consumer demand for products from the new brick business because of the large number of housing and other buildings. And then the lowest increase was only 10,2% due to the decline in purchasing power of new business products in Sungai Buluh Village. That is expected due to declining economic factors so that people's purchasing power is decreasing. So the profit in the brick business is a new business in producing 40,000 bricks which is Rp. 4.170.000.